2000
DOI: 10.1007/s002770050577
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative endogenous erythropoietin levels and changes in intravascular blood volume in healthy humans

Abstract: There is accumulating evidence of a relationship between changes in intravascular blood volume and endogenous erythropoietin (EPO) levels. In this study, eight healthy adult American Society of Anesthesiologists class-I patients due for prolonged elective surgery were randomised either to preoperative hypervolaemic haemodilution using hydroxyethyl starch, followed by intraoperative crystalloid infusion, or to standard intraoperative normovolaemic fluid balance management using crystalloids (control group). Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…; Breymann et al. ) eventually resulting in substantial reductions in PV and RBCV (Fortney et al. ).…”
Section: Introductionsupporting
confidence: 71%
“…; Breymann et al. ) eventually resulting in substantial reductions in PV and RBCV (Fortney et al. ).…”
Section: Introductionsupporting
confidence: 71%
“…However, additional non-hypoxic feedback mechanisms must also regulate EPO production since arterial O 2 partial pressure and renal blood flow/O 2 consumption seldom fluctuate to values required to substantially increase the synthesis of EPO in healthy individuals (Halperin et al, 2006; Perez-Padilla et al, 2006). Among potential non-hypoxic factors related to erythropoiesis, EPO concentrations run inversely to CVP, a variable reflecting the filling state of the cardiovascular system (Ehmke et al, 1995; Gunga et al, 1996; Breymann et al, 2000). In this respect, early animal studies observed a 1.5-fold acute increase in plasma EPO levels following a reduction of blood volume (20%) and CVP while hematocrit was unaltered (Ehmke et al, 1995).…”
Section: Regulation Of Erythropoietin (Epo) Synthesis Through Blood Vmentioning
confidence: 99%
“…In this respect, early animal studies observed a 1.5-fold acute increase in plasma EPO levels following a reduction of blood volume (20%) and CVP while hematocrit was unaltered (Ehmke et al, 1995). In humans, hypervolemic hemodilution increasing CVP paralleled a decrease in circulating EPO seemingly beyond the dilution effect (Breymann et al, 2000). Recently, plasma EPO concentration was found increased independent of hemoconcentration, with moderate head-up tilt redistributing blood toward the lower limbs and thereby reducing CVP (Montero et al, 2016b).…”
Section: Regulation Of Erythropoietin (Epo) Synthesis Through Blood Vmentioning
confidence: 99%
“…We then used published values of BNP and EPO concentrations in similar patients [21, 30] to calculate the number of patients needed (three groups of patients with hypervolemia, normovolemia and hypovolemia, respectively, considering the initial protocol with a 50 % between-group difference and power of 80 %). Data were analyzed using R [31].…”
Section: Methodsmentioning
confidence: 99%
“…Several plasmatic biomarkers may contribute to arbitrating conflict between the control of optimal blood volume and the development of fluid overload: these include stress hormones, such as cortisol and catecholamines; hormones involved in volume regulation by sodium chloride or water retention, such as the renin-angiotensin II-aldosterone system [19]; vasopressin, expressed by (CT)-pro-arginine vasopressin, known as copeptin [20]; endothelin expressed by pro-endothelin and atrial natriuretic peptide (ANP), measured by pro-ANP; factors involved in the production of red blood cells, such as erythropoietin (EPO) [21]; and factors that repair the endothelium after injury, such as mid-regional pro-adrenomedullin (MR-proADM) [22, 23]. …”
Section: Introductionmentioning
confidence: 99%